2005
DOI: 10.1002/eji.200525982
|View full text |Cite
|
Sign up to set email alerts
|

p53 is required for spontaneous autoantibody production in B6/lpr lupus mice

Abstract: The p53 tumor suppressor molecule triggers a key pathway of apoptosis in injured cells, in part through induction of Fas. The importance of Fas as a receptor mediating apoptosis is highlighted by the lupus-like systemic autoimmunity seen in animals and humans with nonfunctional Fas molecules. We set out to see if the absence of p53, superimposed on the Fas defect of lpr mice, might further accelerate or exacerbate their systemic autoimmunity. We generated double mutant mice (p53 -/-lpr) having defects in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Studies have provided evidence that p53 is required for spontaneous autoantibody production in B6/lpr lupus mice [82]. Generation of double mutant mice ( p53 −/− lpr ) having defects in both p53- and Fas-dependent pathways revealed that these mice have lower autoantibody levels than the single mutant lpr mice.…”
Section: The P202 Proteinsmentioning
confidence: 99%
“…Studies have provided evidence that p53 is required for spontaneous autoantibody production in B6/lpr lupus mice [82]. Generation of double mutant mice ( p53 −/− lpr ) having defects in both p53- and Fas-dependent pathways revealed that these mice have lower autoantibody levels than the single mutant lpr mice.…”
Section: The P202 Proteinsmentioning
confidence: 99%
“…Given that type I IFNs increase p53 levels [27], which remain transcriptionally inactive, it remains unclear whether p53 in lymphocytes of SLE patients remains transcriptionally active or not. Moreover, p53 is required for spontaneous autoantibody production in B6/lpr lupus-prone mice [28]. In contrast, mice null for the Gadd45a gene develop lupus-like disease [29] and loss of expression of p21 WAF1 (encoded by the p21 gene), a known transcriptional target of p53, is also linked to the development of autoimmunity [30].…”
Section: P53 In B Cell Survival and Slementioning
confidence: 99%
“…Recently, the process of cell death has been suggested as the source of the antigenic stimulus that drives the production of anti-DNA antibodies in lupus [7-9]. Under normal conditions, the rapid and efficient clearance of apoptotic cells and their debris may prevent this form of self-immunization.…”
Section: Introductionmentioning
confidence: 99%